2017
DOI: 10.1016/j.jvs.2016.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Carotid endarterectomy should not be based on consensus statement duplex velocity criteria

Abstract: Objective Randomized trials support carotid endarterectomy (CEA) in asymptomatic patients with ≥60% internal carotid artery (ICA) stenosis. The widely referenced Society for Radiologists in Ultrasound Consensus Statement on carotid duplex ultrasound (CDUS) imaging indicates that an ICA peak systolic velocity (PSV) ≥230 cm/s corresponds to a ≥70% ICA stenosis, leading to the potential conclusion that asymptomatic patients with an ICA PSV ≥230 cm/s would benefit from CEA. Our goal was to determine the natural hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Two recent meta-analyses investigated the risks and benefits of heparin reversal by protamine after carotid endarterectomy (CEA). 1,2 They found that heparin reversal with protamine reduces the risk for reoperation due to bleeding without an increased risk of stroke, myocardial infarction, or death. Yet, we would like to address the hemostatic and hemodynamic effects of protamine.…”
Section: A Critical Note On Protamine Use In Carotid Endarterectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent meta-analyses investigated the risks and benefits of heparin reversal by protamine after carotid endarterectomy (CEA). 1,2 They found that heparin reversal with protamine reduces the risk for reoperation due to bleeding without an increased risk of stroke, myocardial infarction, or death. Yet, we would like to address the hemostatic and hemodynamic effects of protamine.…”
Section: A Critical Note On Protamine Use In Carotid Endarterectomymentioning
confidence: 99%
“…Columbo and colleagues reported a favorable prognosis for medically managed patients with evidence of an internal carotid artery stenosis between 70% and 80% on ultrasound. 1 However, there is no evidence that neurologic risk is higher in patients above 80% stenosis than in those with stenosis between 70% and 80%. We believe other parameters that can be obtained from transcranial Doppler ultrasound may be more useful in identifying those patients at risk of stroke who would benefit from carotid endarterectomy.…”
mentioning
confidence: 99%
“…3 Up to 90% of CEAs are performed on asymptomatic patients in the United States, in stark contrast to Canada and Europe, where 70% or fewer CEAs are performed on asymptomatic patients (eg, 40.4% in Switzerland, 16.8% in the United Kingdom, 0.0% in Denmark). 4 In their article, Columbo et al 5 derive recommendations from their data that, if followed, would change practice in the United States. Their results and their recommendations raise questions about how asymptomatic patients are diagnosed and treated in this country.…”
mentioning
confidence: 99%
“…The foundation for diagnosis in the Columbo study 5 is carotid duplex ultrasound examination, as it was for the Asymptomatic Carotid Atherosclerosis Study (ACAS) and for the Carotid Revascularization Endarterectomy vs Stenting Trial (CREST). In those trials, attempts were not made to include an intermediate stenosis group or exclude a more severe stenosis group.…”
mentioning
confidence: 99%
See 1 more Smart Citation